Non-Benign Familial Neonatal Convulsions - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
An electroclinical pattern characteristic of benign familial neonatal convulsions is reported in two neonates with non-benign seizures treated at the Miami Children's Hospital, FL Ten seizures recorded by continuous video-EEG telemetry began with generalized tonic posturing and diffuse attenuation of EEG activity.